2018
DOI: 10.1021/acscatal.8b00413
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Catalysis of Electrochemical Overall Water Splitting in Alkaline Media by Fe Doping in Ni3S2 Nanosheet Arrays

Abstract: The development of bifunctional electrocatalysts with high performance for both hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) with earth-abundant elements is still a challenge in electrochemical water splitting technology. Herein, we fabricated a free-standing electrocatalyst in the form of vertically oriented Fe-doped Ni3S2 nanosheet array grown on three-dimensional (3D) Ni foam (Fe-Ni3S2/NF), which presented a high activity and durability for both HER and OER in alkaline media. On the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
281
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 546 publications
(297 citation statements)
references
References 84 publications
15
281
1
Order By: Relevance
“…The HRTEM image indicates the formation of an oxidation layer about 6 nm on the nanowire surface (Figure S7d), whereas a new peak presented at 556 cm À 1 on the Raman spectrum is resulted from NiOOH formation under the high anodic oxidation potential ( Figure S7e). [23,39] In Ni 2p spectrum, two new peaks appeared at 857.8 and 875.5 eV are agreed with Ni 3 + ( Figure S7f), further implying the presence of NiOOH on the surface of the catalyst. [51,52] Meanwhile, the peaks belonged to metallic Ni are disappeared, consistent with a previous report.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…The HRTEM image indicates the formation of an oxidation layer about 6 nm on the nanowire surface (Figure S7d), whereas a new peak presented at 556 cm À 1 on the Raman spectrum is resulted from NiOOH formation under the high anodic oxidation potential ( Figure S7e). [23,39] In Ni 2p spectrum, two new peaks appeared at 857.8 and 875.5 eV are agreed with Ni 3 + ( Figure S7f), further implying the presence of NiOOH on the surface of the catalyst. [51,52] Meanwhile, the peaks belonged to metallic Ni are disappeared, consistent with a previous report.…”
Section: Resultsmentioning
confidence: 66%
“…[10][11][12][13][14][15][16][17] Nickel sulfide with suitable element doping can modulate its electronic and surface structure, hence, significantly enhancing the electrocatalytic performance for OER and (or) HER. Zn, [18] V, [19] Sn, [20] N, [21] Mo, [22] and Fe [23][24][25][26][27][28] elements have been doped in nickel sulfide lattices for promoted OER, HER or overall water splitting electrocatalysis. Interestingly, it is found that the electrochemically oxidized transition metal chalcogenides can improve their catalytic performances for OER.…”
Section: Introductionmentioning
confidence: 99%
“…[14,[28][29] The (101) facet of CoP acts as the active surface because it has proved to have better catalytic activity. Generally, ΔG H* of the catalyst is a good indicator of the activity in HER and ΔG H* of the catalyst approaching zero facilitates proton/electron-transfer and hydrogen release.…”
Section: Hydrogen Evolution Reaction On Wà Cop/ccmentioning
confidence: 99%
“…[14,[28][29] The (101) facet of CoP acts as the active surface because it has proved to have better catalytic activity. [29] ΔG H2O* of WÀ CoP is À 0.543 eV (Figure 4b) which is much larger than that of CoP (À 0.444 eV) indicating a more favorable water activation process on WÀ CoP and improved HER activity in the alkaline medium. Figure 4a presents the ΔG H* of the WÀ CoP and CoP catalysts.…”
Section: Hydrogen Evolution Reaction On Wà Cop/ccmentioning
confidence: 99%
“…[1,7] Considering that surfaces or interfaces play the key role in electrochemical reactions, the morphology, surface defects or interfaces, and electrical structures are the key factors on the electrocatalytic performances of efficient catalysts. [16,17] In particular, in situ growing nanosheet nanostructures on conductive substrates, such as Ni foam, carbon cloth, and stainless steel, could supply the efficient pathways for charge transport and provide open channels for rapid release of gas bubbles during OER or HER process. [16,17] In particular, in situ growing nanosheet nanostructures on conductive substrates, such as Ni foam, carbon cloth, and stainless steel, could supply the efficient pathways for charge transport and provide open channels for rapid release of gas bubbles during OER or HER process.…”
mentioning
confidence: 99%